-7(4x+6)=-(5x+1)

Simple and best practice solution for -7(4x+6)=-(5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(4x+6)=-(5x+1) equation:



-7(4x+6)=-(5x+1)
We move all terms to the left:
-7(4x+6)-(-(5x+1))=0
We multiply parentheses
-28x-(-(5x+1))-42=0
We calculate terms in parentheses: -(-(5x+1)), so:
-(5x+1)
We get rid of parentheses
-5x-1
Back to the equation:
-(-5x-1)
We get rid of parentheses
-28x+5x+1-42=0
We add all the numbers together, and all the variables
-23x-41=0
We move all terms containing x to the left, all other terms to the right
-23x=41
x=41/-23
x=-1+18/23

See similar equations:

| d+36=58 | | 2x+12+19=x+16 | | 25-a=2 | | 2.5x+30=150 | | t-23=24 | | w-8=15 | | 2y-4=13 | | 4^1-2x=0.0625 | | 22x=66x= | | 100=t+25 | | 114=3(y+1 | | 2π(9)+2π(3)(8)=s | | 2(3.14)(9)+2(3.14)(3)(7)=s | | 5+20m−2m=-13 | | t+15=99 | | 56+68+x+66=180 | | 3x​ +1=11 | | x^2=9*15 | | 3.6/x=10.8/12 | | 15q=60,q= | | ​3​​x​​-11=-5 | | 12x−1=11 | | 5^7•5n=5^10 | | 9x-7=-9+15 | | -x2-5x+1=22 | | 0.5=0.2+x-0.2x | | 6b+4b+40=180 | | 25^3r=5^3 | | 6b+4b=40 | | 3a+3a+48=180 | | 509.17=220+1.19x | | 7(y-7)=21 |

Equations solver categories